Travel Medicine - Series 1 - Goodyer, Larry (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This collection of papers describes the recent development of travel health and vaccination services delivered by pharmacists. It is the first dedicated collection of its type and provides a template for the continued growth of pharmacy practice in this area. The articles examine and report on aspects of such services in the UK, US, Canada, Australia, Switzerland, and South Africa, which will provide useful insight for those in other countries developing such pharmacy-based services.